The Bachelor of Science in Accountancy Program of the University of Santo Tomas – Legazpi: A Program Review and Analysis - Yanzon, Celeste T.; Mortola, Tressa Adelfa M.; Nacion, Marilou O. (Future Science / FSH-PH Publications, 2025)
The study looked into the Bachelor of Science in Accountancy (BSA) program of the University of Santo Tomas—Legazpi, specifically the provision of services classified into two major aspects: contextual and administration and management support, geared towards improving the performance of its graduates in the Licensure Examination for Certified Public Accountants (LECPA). Contextual aspects include classroom conditions, curriculum and instruction, admission and retention policies, internship requirements, off-campus activities, and library resources. Administration and management consist of moral and spiritual upliftment, financial support, facilities and services provision, and academic policies. It made use of the descriptive method with thirty-two (32) BSA graduating students surveyed through an electronically mailed researcher-prepared questionnaire. Frequency count, percentage, and weighted mean utilizing Likert scale were employed as statistical tools. A five-point rating scale for determining the learning environment's status and its effect on the respondents' readiness for the licensure examination was utilized. The results reveal that the institution has adequate and functional provisions in all aspects except in the areas of curriculum and instruction considered to be only moderate/acceptable. The areas of instructional competence and instruction were studied as having a very high impact, with a relationship existing between the latter and the readiness to take the board examination. The study recommends adopting intervention measures that include the modification of the existing curriculum; the objective evaluation and upgrade of admission and retention requirements to reasonable levels; and the continuous review, appraisal, and improvement of existing standards of instruction.